2013
DOI: 10.1136/gutjnl-2013-304701
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and colorectal cancer

Abstract: Excess body weight, as defined by the body mass index (BMI), has been associated with several diseases and includes subjects who are overweight (BMI ≥ 25-29.9 kg/m(2)) or obese (BMI ≥ 30 kg/m(2)). Overweight and obesity constitute the fifth leading risk for overall mortality, accounting for at least 2.8 million adult deaths each year. In addition around 11% of colorectal cancer (CRC) cases have been attributed to overweight and obesity in Europe. Epidemiological data suggest that obesity is associated with a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
509
2
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(540 citation statements)
references
References 185 publications
(176 reference statements)
16
509
2
13
Order By: Relevance
“…It is generally accepted that cigarette smoking plays an important role in lung carcinogenesis (4). In addition, epidemiological data suggested that obesity is associated with an increased risk of colon cancer (10). Diabetes and high dietary meat intake are also associated with an increased risk of colon cancer (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that cigarette smoking plays an important role in lung carcinogenesis (4). In addition, epidemiological data suggested that obesity is associated with an increased risk of colon cancer (10). Diabetes and high dietary meat intake are also associated with an increased risk of colon cancer (11).…”
Section: Discussionmentioning
confidence: 99%
“…We can see from the survey that the incidence of colorectal cancer in urban areas is obviously higher than in rural areas (26.70/100,000 in urban and 15.01/100,000 in rural), which can be attributed to the dietary habits, different life-style and air pollution (Dai et al, 2007;Guh et al, 2009;Harriss et al, 2009;Bardou et al, 2013;Johnson et al, 2013). The people in urban areas are more likely to eat meat, high-sugar drinks, no-fiber foods and irregular eating habits (Guh et al, 2009;Harriss et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers suppose that metabolic syndromes, insulin resistance, modified adipocitokine levels and molecular mediators are involved, although these mechanisms too have not been established to-date. One of the hypotheses suggests high insulin levels and insulin-related growth factors favour CRC development [20]. Recently published research has focused on the involvement of inflammatory processes, adipokines and estrogens in CRC.…”
Section: Discussionmentioning
confidence: 99%